Pengembangan Media Belajar Pendidikan Jasmani Materi Guling Depan Pada Mahasiswa Pendidikan Jasmani Semester III Universitas Muhammadiyah Mahakarya Aceh - Zainal Abidin; Arda Tonara; Budiman Budiman; Bambang Eko Prayetno (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The research titled "Development of Physical Education Learning Media for Forward Roll Material for Third Semester Physical Education Students at UMMAH" aims to produce interactive learning media in the form of a CD for forward roll material. This research uses a qualitative approach, with the population being all third-semester Physical Education students at UMMAH, totaling 26 students as the sample. Data collection techniques include observation and questionnaires. The research results show that: (1)Validation by material and media experts declared the media feasible to use without revision after three and two stages of evaluation, respectively. (2)Students stated that this learning media facilitates understanding and increases learning motivation. The appearance aspect is rated good and simple, while the quality of the text and video is considered easy to understand. The overall average rating of multimedia quality is "very good" with a score of 4.33.